2019
DOI: 10.33417/tsh.572224
|View full text |Cite
|
Sign up to set email alerts
|

Torunlarına Bakan Büyükannelerin Deneyimlerine İlişkin Nitel Bir Araştırma

Abstract: Bu araştırma torunlarının bakımını gerçekleştiren büyükannelerin bakım süreciyle ilgili deneyimlerini keşfetmek amacıyla nitel araştırma yöntem ve teknikleri kullanılarak gerçekleştirilmiştir. Kartopu örnekleme yöntemiyle ulaşılan 15 büyükanne ile derinlemesine görüşmeler gerçekleştirilmiştir. Derinlemesine görüşmelerle oluşturulan veriler nitel veri analiz programı olan MAXQDA ile analiz edilmiştir. Analiz sonucunda büyükanneliğe atfedilen anlam, torun bakımına karar verme süreci, büyükannelerin torun bakım s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Moreover, spending time with grandchildren has a pleasing effect on grandparents. 14,15 Studies show that caring for grandchildren brings positive feelings and situations to the fore for grandparents. For instance, Uğur 16 found that grandparents' caring for their grandchildren gives them a sense of "psychological satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, spending time with grandchildren has a pleasing effect on grandparents. 14,15 Studies show that caring for grandchildren brings positive feelings and situations to the fore for grandparents. For instance, Uğur 16 found that grandparents' caring for their grandchildren gives them a sense of "psychological satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Grandparents also have an important influence on their grandchildren. Moreover, spending time with grandchildren has a pleasing effect on grandparents 14,15 . Studies show that caring for grandchildren brings positive feelings and situations to the fore for grandparents.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, grandparents are generally happy to take care of their grandchildren. In a study of grandmothers, participants stated that they see the care of grandchildren as a sacred duty given to them despite its difficulties, which shows that they tend to focus more on the positive aspects of this task (Tas ¸kın & Akçay, 2019). The preference of relying on grandparents for childcare and the willingness of grandparents to provide it can be explained by families' sociocultural characteristics.…”
Section: Grandparenting Role and Childrearing In Turkeymentioning
confidence: 99%